Interleukine-6 Level in Saliva of Patients with Chronic Periodontitis: A Case-Control Study - Haween T Nanakaly (College of Dentistry/ University of Baghdad, 2016)
Background:Periodontal diseases are infectious diseases in which periodontalpathogens trigger chronic inflammatory and immune responses. Interleukine-6 is a multifunctional cytokine playing a central role in inflammation and tissue injury.The aim of the study IS to determine the level of Interleukin-6(IL-6) in saliva of patients with chronic periodontitis compared to healthy subjects. Materials and Methods:The total subjects of the present study is 60, divided into 3 groups; 20 patients with chronic periodontitis with pocket depth(PD ≥4 mm)(group I), 20 patients with pocket depth(PD